Acute Generalized Exanthematous Pustulosis: An Unusual Case due to Spider Bite - Mehreen Ghafoor Chaudhri; Najia Ahmed; Tariq Mahmood malik; Syed Arbab Shah; Mehwish Hira (Pakistan Armed Forces Medical Journal, 2023)
Acute generalized exanthematous pustulosis is an infrequent but severe pattern of cutaneous adverse reaction. It is characterized by the sudden appearance of sterile pustules on edematous-erythematous skin, which is mostly caused by the consumption of medications. However, it may also be associated with viral infections, toxins, or food allergens, although this is rare. We reported a case of AGEP in a 33-year-old male shortly after a spider bite, a rare cause of AGEP. It was improved by oral corticosteroid treatment after seven days.